The Influence of Financial Performance on Company Value with Debt to Equity as a Moderating Variable - Frisca Fitriana Lulfi; Erma Setiawati (SEIKO : Journal of Management & Business, 2026)
This research endeavor seeks to investigate the influence of financial performance on corporate value, utilizing the Debt to Equity Ratio (DER) as a moderating variable. Financial performance is represented through the proxies of Return on Equity (ROE) and Return on Assets (ROA), while corporate value is quantified via total equity. The investigation employs secondary data derived from 44 companies in the basic materials sector that are listed on the Indonesia Stock Exchange over the period from 2022 to 2024, culminating in a total of 132 panel observations. The analysis adopts panel data regression techniques, specifically incorporating Moderated Regression Analysis (MRA) to evaluate the proposed hypotheses. The findings reveal that ROA exerts a positive and statistically significant impact on corporate value, whereas ROE demonstrates a negative and statistically significant effect when the moderating variable is factored in. Moreover, the DER serves as a significant moderator in the relationship between ROE and ROA concerning corporate value, thereby underscoring the critical role of capital structure in intensifying or diminishing the influence of profitability on corporate value. These results underscore the necessity for effective asset management and an optimal capital structure to enhance corporate value within the basic materials industry.